Expressive Intersections in Brahms : Essays in Analysis and Meaning - Smith, Peter Howard; Platt, Heather Anne (Book collections on Project MUSE., 2012)
Contributors to this exciting new volume examine the intersection of structure and meaning in Brahms's music, utilizing a wide range of approaches, from the theories of Schenker to the most recent analytical techniques. They combine various viewpoints with the semiotic-based approaches of Robert Hatten, and address many of the most important genres in which Brahms composed. The essays reveal the expressive power of a work through the comparison of specific passages in one piece to similar works and through other artistic realms such as literature and painting. The result of this intertextual r.